Exploring how nutrition & dietetic students make meaning of their educational experiences and the impact it has on their leadership development - Murray, Sarah Elizabeth (Kansas State University, 2022)
Leadership development for the nutrition and dietetics profession has been widely discussed as an important need to propel the profession forward. Leadership skills and competencies are included in the standardized curriculum for nutrition and dietetic students; however, little guidance exists on how to foster leadership development. Self-authorship is a development theory that is used to describe how an individual makes meaning of their own experiences, establishes an identity, and responds to others through internal influences rather than external factors. Self-authorship provides a unique framework in which to view the development of leadership behaviors. Using a constructivist grounded theory approach, this qualitative study explored how students describe and make meaning of their educational experiences and the contributing factors to their leadership development. Seventeen participants who graduated with a Bachelor of Science degree in nutrition and dietetics from a public Mid-western university were interviewed. Program artifacts from the research site were also collected for data analysis. Leadership development of the participants was explored through the lens of developmental theory. Four themes emerged that participants identified as required building blocks for leadership development: knowledge, observation, emulation, and self-efficacy. Most of the participants were confident in their abilities and preparedness to serve as a leader in the profession; however, they lacked a leadership identity creating a barrier to serve at this point in their professional journey.
Keywords: Dietetics education; Constructivism; Leadership; Leadership identity